Covid-19 Incidence Rates Decreased in Ramadhan Season during Applied Large-Scale Social Distancing in Jakarta, Indonesia - Meita Veruswati; Rony Darmawansyah Alnur; Al Asyary (JUMP Health (Journal of Ultimate Public Health), 2020)
Background: At the same time of Covid-19’s transmission peak, Indonesia, as the biggest Moslem population in the world, is facing the holy month of the Ramadhan that contained more praying and religious traditional habits in mass gathering setting. As of social distancing was implementing, this study aims to present the difference between before and during Ramadhan with Covid-19 incidence rates while the implementation of large-sale social distancing (LSSD) was applied. Method: This study was using the dataset which was obtained from Covid-19 reports from the authorities, comprising of the local government of Jakarta and the Indonesian Ministry of Health. The Covid-19 cases were studied in this research: incidence and suspect which were showed in daily rates with before and during Ramadhan while LSSD was applied in Jakarta, Indonesia. Results: There is a difference that happens significantly with the rate of positive confirmed patients before and during Ramadhan while LSSD (p-value = 0.049; mean difference = 33.310). Conclusion: This research presented that the rate of Covid-19 cases decreased during Ramadhan season as social distancing effective to control potential religious and tradition mass gathering in Jakarta, Indonesia.